2015
DOI: 10.1002/prca.201400114
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in bodily fluids are a highly stable resource of disease biomarkers

Abstract: Biomarkers are measurable indicators of a biological state. As our understanding of diseases meliorates, it is generally accepted that early diagnosis renders the best chance to cure a disease. In the context of proteomics, the discovery phase of identifying bonafide biomarkers and the ensuing validation phase involving large cohort of patient samples are impeded by the complexity of bodily fluid samples. High abundant proteins found in blood plasma make it difficult for the detection of low abundant proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
389
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(398 citation statements)
references
References 89 publications
5
389
0
4
Order By: Relevance
“…Therefore, considerable focus has shifted to studying and identifying cancerspecific molecular signatures that can be utilized for detection of the disease at an early stage. To this end, much like circulating tumor cells, exosomes carry a wealth of information about the disease characteristics in the form of proteins, lipids, nucleic acids and metabolites that are shed from tumor cells into the exosomes [98]. Besides being secreted by different types of cells in vitro, studies have confirmed the presence of exosomes from various biological fluids including blood, urine, saliva, ascites, cerebrospinal fluid, synovial fluid, breast milk, and bronchoalveolar lavage [99].…”
Section: Exosomes In Cancer Biomarker Screeningmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, considerable focus has shifted to studying and identifying cancerspecific molecular signatures that can be utilized for detection of the disease at an early stage. To this end, much like circulating tumor cells, exosomes carry a wealth of information about the disease characteristics in the form of proteins, lipids, nucleic acids and metabolites that are shed from tumor cells into the exosomes [98]. Besides being secreted by different types of cells in vitro, studies have confirmed the presence of exosomes from various biological fluids including blood, urine, saliva, ascites, cerebrospinal fluid, synovial fluid, breast milk, and bronchoalveolar lavage [99].…”
Section: Exosomes In Cancer Biomarker Screeningmentioning
confidence: 95%
“…The complexity of the plasma protein content poses a considerable hurdle in this developmental path since the useful biomarkers are often in a very low concentration and are dominated by other abundant proteins [98]. Exosomes on the other hand provide a much cleaner clinical sample devoid of plasma proteins and thus make the analysis and biomarker validation easier.…”
Section: Exosomes In Cancer Biomarker Screeningmentioning
confidence: 99%
“…Indeed, EVs are emerging as a unique mechanism for enriching low-level antigens for cancer diagnosis (76), and recent studies using T. cruzi-specific RNA aptamers detected antigens in TESA preparations or serum from mice with acute or chronic T. cruzi infection (77).…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of extracellular vesicles (EVs), including microvesicles and exosomes, and their potentially important cellular functions in tumor biology and metastasis has presented them as intriguing sources for biomarker discovery and disease diagnosis (4)(5)(6). Critical for immune regulation and intercellular communication, EVs have many differentiating characteristics of cancer cell-derived cargo, including mutations, active miRNAs, and signaling molecules with metastatic features (7,8).…”
mentioning
confidence: 99%